Analysis of the Application of PSAK 241 to Biological Assets and Its Implications for the Quality of Financial Statements at PT. Karya Semangat Mandiri - Ive Manta Br Lingga; Laylan Syafina; Nurwani (Cakrawala Repositori IMWI)
Accounting is a process that involves recording, processing, and presenting financial information so that the data generated in financial reports can be used by users as a basis for decision-making. Financial statements must be prepared in accordance with applicable Pernyataan Standar Akuntansi Keuangan (PSAK) and possess the characteristics of relevance, reliability, accuracy, credibility, and understandability for users. This study aimed to analyze the implementation of PSAK 241 on biological assets and its implications for the quality of financial reporting at PT Karya Semangat Mandiri. The study employed a qualitative approach using a descriptive case study method. Data were collected through interviews, documentation, and financial statement analysis, and were analyzed using interactive analysis techniques. The results showed that the company had implemented PSAK 241 in the recognition, measurement, presentation, and recognition of gains or losses based on fair value. However, inconsistencies remained in the disclosure aspect, particularly regarding the classification of biological assets and mortality information. These limitations affected the transparency of financial reporting. Therefore, improvements in disclosure practices are necessary to enhance the relevance and reliability of financial statements.